The use of essential oils in veterinary ectoparasite control: a review. Issue 3 (22nd October 2013) - ELLSE, L.; WALL, R.
Abstract There is a growing body of evidence indicating the potential value of essential oils as control agents against a range of arthropod ectoparasites, particularly lice, mites and ticks. Toxicity has been demonstrated following immersion and physical contact with treated surfaces, as well as after exposure to the vapour of these oils; the last of these factors implies that there is a neurotoxic, rather than simply a mechanical, pathway in their mode of action. However, the volatile nature of essential oils suggests that their residual activity is likely to be short‐lived. A possible advantage of essential oils over conventional ectoparasite treatments may refer to their reported ovicidal efficacy, although it is unclear whether this results from neurotoxicity or mechanical suffocation. There are many difficulties in comparing the findings of existing studies of essential oil toxicity. One major issue is the wide variation among batches in the relative concentrations of oil constituents. A second issue concerns the fact that many experimental designs make it difficult to confirm that the effect seen is attributable to the oil; in many cases inappropriate controls mean that the effects of the excipient on mortality cannot be distinguished. Hence, it is important that an excipient‐only control is always included in these bioassays. Furthermore, in direct contact assays, when attempting to identify the toxicity pathway of the essential oil tested, it is important to include a hydrophobic control. Without this, it is impossible to distinguish simple mechanical effects from neurological or other cellular toxicity. The use of essential oils in the control of veterinary ectoparasites is an area which holds considerable potential for the future and research into their use is still at an early stage. More extensive field trials, the standardization of components, the standardization of extraction, the standardization of good experimental design, mammalian toxicology profiling and excipient development, as well as further investigation into the residual activities and shelf‐lives of these oils are all required to allow the full realization of their potential.